A summation formula concerning the Mellin Transform - Glasser, M.; Bagis, Nikos; Majchrowska, Grazyna (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
We derive a new summation formula involving Mellin transform. We apply this formula to sum various series related to elliptic integrals and theta functions.